2016
DOI: 10.1073/pnas.1504887113
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the gut microbiota modulates the severity of malaria

Abstract: Plasmodium infections result in clinical presentations that range from asymptomatic to severe malaria, resulting in ∼1 million deaths annually. Despite this toll on humanity, the factors that determine disease severity remain poorly understood. Here, we show that the gut microbiota of mice influences the pathogenesis of malaria. Genetically similar mice from different commercial vendors, which exhibited differences in their gut bacterial community, had significant differences in parasite burden and mortality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
283
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(303 citation statements)
references
References 43 publications
17
283
2
1
Order By: Relevance
“…Interestingly, CD40 signaling was not absolutely essential for ECM development, as CD40L-deficient mice eventually developed ECM in the absence of added PbT-II T cells, although with a delayed kinetics. This contrasts a previous report that found CD40L-deficient mice were resistant to ECM (94), an observation that may be explained by differences in animal housing facilities, potentially microbiota, known to affect ECM (95). In summary, our work extends earlier findings by determining that CD4 + T cell help is required for optimal CD8 + T cell expansion after infection with different doses of parasites, and is relatively independent of the initial CD8 + T cell precursor frequency.…”
Section: Discussioncontrasting
confidence: 86%
“…Interestingly, CD40 signaling was not absolutely essential for ECM development, as CD40L-deficient mice eventually developed ECM in the absence of added PbT-II T cells, although with a delayed kinetics. This contrasts a previous report that found CD40L-deficient mice were resistant to ECM (94), an observation that may be explained by differences in animal housing facilities, potentially microbiota, known to affect ECM (95). In summary, our work extends earlier findings by determining that CD4 + T cell help is required for optimal CD8 + T cell expansion after infection with different doses of parasites, and is relatively independent of the initial CD8 + T cell precursor frequency.…”
Section: Discussioncontrasting
confidence: 86%
“…Sebina et al also recently reported reduced parasitemia in IFNAR -/-mice as compared with control mice infected with P. yoelii 17XNL starting at day 14 after infection (28). Another potential explanation for different experimental outcomes could be either mouse strain differences or differences in the microbiome, both of which have substantial effects on the host response to infection in murine models of blood-stage malaria (77)(78)(79). We used littermate controls to minimize the contribution of microbiome or strain background to our observations.…”
Section: Discussionmentioning
confidence: 99%
“…To examine antigen-specific CD4 + T cells responding to infection, P. yoelii were generated that constitutively express the Lymphocytic choriomeningitis virus-derived (LCMV-derived) glycoprotein (GP) epitope (GP [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] ). This allows for the identification and analysis of antigen-specific CD4 + T cells using previously described GP66:I-A B tetramer enrichment strategies (16).…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial endosymbiont, Wolbachia, for example, enhances resistance to Drosophila C virus in flies 10,131 and to dengue and chikungunya virus infections in mosquitoes 132 ( Figure 5). Symbiotic interactions between bacteria and mice can also promote immune-driven resistance mechanisms against viral 133 , bacterial 134 or protozoan 135,136 infections ( Figure 5). This argues that the establishment of stable symbiotic interactions between microcellular and multicellular organisms is a widespread recurrent trait that modulates host resistance against a variety of pathogens ( Figure 5).…”
Section: Box 3 Microbiota and Disease Tolerancementioning
confidence: 99%
“…Symbiotic neomycin-sensitive bacteria can promote immune-driven resistance mechanisms against influenza A virus infection in mice, via mechanism involving bacterial sensing by inflammasomes 133 . The gut E. coli O86B7 commensal elicits an IgM antibody response directed against the galα(1,3)gal glycan that confers resistance to Plasmodium infection in mice and possibly in humans 135 while Lactobacillus and Bifidobacterium confer resistance to Plasmodium infection in mice via a mechanism that has not been clearly established 136 . Other gram-negative bacterial components of the mouse gut microbiota are sensed by TLR4 and trigger an antigen-specific IgG antibody responses directed against Murein lipoprotein, which confer resistance to systemic E. coli infection 134 .…”
Section: Box 3 Microbiota and Disease Tolerancementioning
confidence: 99%